Tracing Water Sources and Fluxes in a Dynamic Tropical Environment: From Observations to Modeling - Sánchez-Murillo, Ricardo; Esquivel-Hernández, Germain; Birkel, Christian; Correa, Alicia; Welsh, Kristen; Durán-Quesada, Ana María; Sánchez-Gutiérrez, Rolando; Poca, María (Frontiers in Earth Science, 2020)
Tropical regions cover approximately 36% of the Earth’s landmass. These regions are home to 40% of the world’s population, which is projected to increase to over 50% by 2030 under a remarkable climate variability scenario often exacerbated by El Niño Southern Oscillation (ENSO) and other climate teleconnections. In the tropics, ecohydrological conditions are typically under the influence of complex land-ocean-atmosphere interactions that produce a dynamic cycling of mass and energy reflected in a clear partition of water fluxes. Here, we present a review of 7 years of a concerted and continuous water stable isotope monitoring across Costa Rica, including key insights learned, main methodological advances and limitations (both in experimental designs and data analysis), potential data gaps, and future research opportunities with a humid tropical perspective. The uniqueness of the geographic location of Costa Rica within the mountainous Central America Isthmus, receiving moisture inputs from the Caribbean Sea (windward) and the Pacific Ocean (complex leeward topography), and experiencing strong ENSO events, poses a clear advantage for the use of isotopic variations to underpin key drivers in ecohydrological responses. In a sequential approach, isotopic variations are analyzed from moisture transport, rainfall generation, and groundwater/surface connectivity to Bayesian and rainfall-runoff modeling. The overarching goal of this review is to provide a robust humid tropical example with a progressive escalation from common water isotope observations to more complex modeling outputs and applications to enhance water resource management in the tropics.